Design of the Android-Based Malaria-Mapping Application Mobfabria - Meiyeriance Kapitan; Pius Selasa; Yohanes C. Nugraha; Karol Octrisdey; Lusia Dalong (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Malaria represents one of the tropical diseases and a health problem in the East Nusa Tenggara (NTT) Province. Malaria cases are still high in some districts in NTT, including East Sumba, Central Sumba, West Sumba, and Southwest Sumba. Infants, children, and pregnant women are the high-risk groups to suffer from malaria. The highest number of cases was recorded in Southwest Sumba district with 4,273 cases in November 2022. This situation requires preventive and curative actions to address malaria cases in NTT. These actions include health education and malaria data mapping for high-risk groups in malaria-endemic areas. It is expected that these measures will assist in healthcare services, especially in malaria-endemic areas. Considering the current phenomenon of digital era development, the researchers have designed an Android-based mapping and education application for malaria called “mobfabria”. To develop a prototype of the mobfabria applicatio. This is research and development study. The research was conducted in 2023, where the application test took place from March to April 2023 at the Oemasi Health Center in Kupang District. The research subjects consisted of 5 individuals during the development stage and 15 pregnant women during the evaluation stage. The application created by the researchers can be downloaded from the Play Store: https://play.google.com/store/apps/details?id=com.mobfabria.apps. The research stages are approval, ethical test, instrument test, and application test. The application is developed according to the needs analysis, system design, and database. It was built using Android tools. The assessment by experts in health promotion, media, and malaria practitioners was considered good enough, leading to changes in the application's interface design and data storage units. The data was analyzed descriptively. Mapping and data collection of pregnant women with malaria can be accurately obtained. This application is expected to be used for healthcare services and facilities in malaria-endemic areas.